Characterizing farming systems around Kakamega Forest, Western Kenya, for targeting soil fertility–enhancing technologies - Diwani, T.N.; Asch, F.; Becker, M.; Mussgnug, F. (Wiley, 2013)
Kakamega district in Western Kenya represents the smallholder farming systems typical formuch of the densely populated humid highlands in East Africa. A specific feature, however, isthe presence of a protected forest reserve (Kakamega Forest National Park), covering some20% of the district area. Year-round crop production with little use of external inputs is resultingin declining soil fertility and crop yields. Technologies to counteract fertility constraints are rarelyimplemented, as they do not consider system diversity or farm-specific characteristics. Wesurmised that farm type–specific targeting of technology options to address soil fertility–relatedproduction constraints would reduce the anthropogenic pressure on the resources of the adja-cent Kakamega rainforest reserve. Based on Kenyan national census data, we selected 168farms in physical proximity of the Kakamega forest and characterized them regarding productionsystem and soil attributes. Cluster and principal component analyses identified five distinct farmcategories. Three representative farms from each cluster group were subsequently selected toestablish labor-use patterns, draw resource-flow maps, and determine NPK balances.Small subsistence-oriented farms were most common (> 50%), with maize yields of 0.9 t ha–1(Cluster 1). Most farmers relied on the forest to provide fire wood, animal feed, and medicinalplants. Mixed farms, combining subsistence maize with industrial crops, were differentiated bysoil type, with tea being grown on Ferralsol (Cluster 3), and sugar cane being grown on Acrisol(cluster 4). The dependence on forest resources was limited to animal grazing and the collectionof feed stuff (Cluster 3), or the extraction of medicinal plants (Cluster 4). Only few farms showeda high degree of market orientation of the food-crop production. These comprised either smallfarms with high investments in fertilizer and maize yields close to 2 t ha–1(Cluster 2), or largerfarms (1.6–3.9 ha) with low fertilizer but high hired-labor use (Cluster 5). Their reliance on forestresources was generally low. Resource flows showed mainly patterns of nutrient export in sub-sistence farms, and more complex flow patterns, involving several farm compartments, in thediversified farms. Partial nutrient balances were strongly negative for N and K, irrespective ofsoil or farm type. Soil-fertility characteristics reflected the nutrient balances with generally low Cand N in all farms on Acrisol, and low P in farms not applying mineral fertilizers or farmyard man-ure. The proposed typology is expected to improve the targeting of technologies addressing soilfertility–related production constraints, and to reduce the pressure on forest resources. This is ofparticular importance in the case of small-scale subsistence and mixed farms close to the forestmargin.